Long-Term Effects of Maternal Deprivation on the Volume of Dopaminergic Nuclei and Number of Dopaminergic Neurons in Substantia Nigra and Ventral Tegmental Area in Rats - Slobodan Kapor; Milan Aksić; Laslo Puškaš; Marin Jukić; Marin Jukić; Joko Poleksić; Filip Milosavljević; Suncica Bjelica; Suncica Bjelica; Branislav Filipović (Frontiers Media S.A., 2020)
Early life adversities leave long-lasting structural and functional consequences on the brain, which may persist later in life. Dopamine is a neurotransmitter that is extremely important in mood and motor control. The aim of this study was to investigate the effect of maternal deprivation during the ninth postnatal day on the volume of dopaminergic nuclei and the number of dopaminergic neurons in adolescence and adulthood. Maternally deprived and control Wistar rats were sacrificed on postnatal day 35 or 60, and the dopaminergic neurons were stained in coronal histological sections of ventral midbrain with the tyrosine hydroxylase antibody. The volume of dopaminergic nuclei and the number of dopaminergic neurons in the substantia nigra (SN) and ventral tegmental area (VTA) were analyzed in three representative coordinates. Maternal deprivation caused weight loss on postnatal day 21 (weaning) and corticosterone blood level elevation on postnatal days 35 and 60 in stressed compared to control rats. In maternally deprived animals, the volumes of SN and VTA were increased compared to the controls. This increase was accompanied by an elevation in the number of dopaminergic neurons in both nuclei. Altogether, based on somatic and corticosterone level measurements, maternal deprivation represents a substantial adversity, and the phenotype it causes in adulthood includes increased volume of the dopaminergic nuclei and number of dopaminergic neurons.